2019
DOI: 10.1017/brimp.2019.2
|View full text |Cite
|
Sign up to set email alerts
|

Third-Wave Therapies for Long-Term Neurological Conditions: A Systematic Review to Evaluate the Status and Quality of Evidence

Abstract: Background: Adults with long-term neurological conditions can face complex challenges including anxiety and depression. Emerging research suggests the utility of third-wave approaches (the third development of psychotherapies) in working transdiagnostically with these difficulties.Aims: This systematic review sought to summarise and appraise the quality of published empirical studies using third-wave therapies such as Compassion Focused Therapy; Acceptance and Commitment Therapy; and Mindfulness-Based Cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 76 publications
(152 reference statements)
1
6
0
1
Order By: Relevance
“…These results provide evidence for the effectiveness of the MSCBI. Our finding is in line with several studies showing that transdiagnostic treatment approaches significantly reduce emotional distress for patients with neurological conditions 23 , 30 . Moreover, our result indicates that the adapted, shortened, and intense MSCBI for patients with acquired brain injury is feasible and that this population can benefit from the injury-adjusted format.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results provide evidence for the effectiveness of the MSCBI. Our finding is in line with several studies showing that transdiagnostic treatment approaches significantly reduce emotional distress for patients with neurological conditions 23 , 30 . Moreover, our result indicates that the adapted, shortened, and intense MSCBI for patients with acquired brain injury is feasible and that this population can benefit from the injury-adjusted format.…”
Section: Discussionsupporting
confidence: 92%
“…It is also associated with a reduction in symptoms of post-traumatic stress 25 , depression 26 and mental fatigue 27 29 . A recent review concludes that such transdiagnostic psychotherapeutic interventions for patients with neurological conditions can lead to a significant overall reduction in emotional distress, although some studies found mixed results 30 . However, mindfulness- and self-compassion-based interventions are usually challenged by low adherence to treatment and high attrition rates, ranging from 13% up to 61% for patients with acquired brain injury 26 , 28 , 31 – 33 .…”
Section: Introductionmentioning
confidence: 99%
“…However, it is still unclear how cognitive deficits may limit the ability of patients to actually attend psychotherapy or how cognitive problems may preclude a positive response to treatment. Cognitive symptoms such as those related to frontal lobe damage provoke a series of cognitive (e.g., disturbances in attention, planning, rigidity, inertia, criticism, control, inhibition, and decision-making) and emotional deficits (e.g., apathy, abulia, anhedonia, impulsiveness, behavioral inadequacy, aggression, and sociopathy) can greatly impact psychological interventions in patients with neurological disorders (Robinson et al, 2019 ) or acquired brain injury (Thøgersen et al, 2022 ). Psychotherapists have to be aware of executive dysfunction hindering the therapeutic process as an impairment that can strongly restrain its effect (Diamond, 2013 ; Cozolino, 2017 ), specifically in the case of particular approaches designed for older adults because of diminished specific frontal skills reported in elderly (Goodkind et al, 2016 ).…”
Section: Cognitive Psychopathology and Psychotherapymentioning
confidence: 99%
“…Accordingly, our Research Topic includes papers that are consistent with positive psychology and third wave CBT (e.g., mindfulness). Here the emphasis is on changing one's relationship with difficult thoughts (Robinson et al, 2019 ) thereby promoting acceptance and emotional balance as well as building positive emotions. For example, through connection with the present moment as well as through practicing exercises and activities that promote positive emotion (e.g., Tulip et al ; Di Giacomo et al ; Rowlands et al ; Marks et al ; Rodrigues et al ; Wigham et al ).…”
Section: Reducing Illbeing Is Not the Same As Promoting Wellbeingmentioning
confidence: 99%